Qualified female volleyball players special physical training development - Tinyukov, A. B. (The Russian Journal of Physical Education and Sport, 2018)
Annotation. Competitive activity effectiveness increase among volleyball players is a difficult problem and demands a complex many-sided approach to its solution. Qualified female volleyball players` sportsmanship improvement is mainly connected with special physical training development. It provides kinesiological potential realization. During educational-training process organization great attention should be paid to special physical training development. Scientific-methodical literature analysis shows that great opportunities for technical readiness level increase are in muscular power indices, speed-power qualities, spring ability, rhythmicity and other motor-coordinating qualities improvement. Materials. The article is about the conditions, which provide an optimal level of physical readiness among qualified female volleyball players by means of easier, standard and complicated variants of motor tasks fulfillment. It provides more effective qualitative sides of motor activity development. Research methods: scientific-methodical literature analysis, pedagogical experiment, testing, non-standard equipment use, evaluation criteria creation, methods of mathematical statistics. Results. Special additional devices of visual references creation; special motor tasks use for motor rhythm formation are important for qualified female volleyball players` optimal level of physical readiness provision. It conditioned the choice of preparatory and special physical exercises. They provide the leading motor-coordinating qualities indices increase: speed-power, jumping endurance, special dexterity, spring ability, accuracy, body steadiness. Rhythmicity increase is also important for an individual technique of difficult technical methods formation, efficiency of movements, motor and vegetative functions coordination. With special physical readiness indices increase sensory correction was directed toward motor activities specification during the studied technical method fulfillment in volleyball. Conclusion. The results of the pedagogical experiment showed the effectiveness of created by the author methodology of qualified female volleyball players` special physical readiness development and it helped to improve their indices of motor-coordinating qualities.